2014
DOI: 10.1523/jneurosci.2062-14.2014
|View full text |Cite|
|
Sign up to set email alerts
|

When the Brain Takes a Break: A Model-Based Analysis of Mind Wandering

Abstract: Mind wandering is an ubiquitous phenomenon in everyday life. In the cognitive neurosciences, mind wandering has been associated with several distinct neural processes, most notably increased activity in the default mode network (DMN), suppressed activity within the anti-correlated (task-positive) network (ACN), and changes in neuromodulation. By using an integrative multimodal approach combining machine-learning techniques with modeling of latent cognitive processes, we show that mind wandering in humans is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
239
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(278 citation statements)
references
References 68 publications
26
239
0
Order By: Relevance
“…Our model links an active state of mind wandering to reduced activation in the PCC/mPFC and poor task performance (Table 1), which would explain these finger-tapping findings. In contrast, studies that found a positive correlation between mind wandering and PCC/mPFC activity used sustained attention tasks where mind wandering was sampled with thought-probes [2][3][4]13]. In such a setting, it is likely that episodes of mind wandering are relatively sparse and most thought probes where participants indicated they were off-task likely mirrored the state we described as off-focus (exploratory) in this model.…”
Section: Implications Of the Modelmentioning
confidence: 94%
See 4 more Smart Citations
“…Our model links an active state of mind wandering to reduced activation in the PCC/mPFC and poor task performance (Table 1), which would explain these finger-tapping findings. In contrast, studies that found a positive correlation between mind wandering and PCC/mPFC activity used sustained attention tasks where mind wandering was sampled with thought-probes [2][3][4]13]. In such a setting, it is likely that episodes of mind wandering are relatively sparse and most thought probes where participants indicated they were off-task likely mirrored the state we described as off-focus (exploratory) in this model.…”
Section: Implications Of the Modelmentioning
confidence: 94%
“…This operationalization is based on correlations between simultaneously recorded neural activity and pupil diameter [18], and although this link has been somewhat speculative [21,22] the relationship between LC-NE system activity and pupil diameter was recently substantiated with electrophysiological measures in non-human primates [23]. In addition, several studies have investigated pupil diameter in a mind-wandering context: An increase in tonic pupil diameter precedes mind wandering-related errors [14], and a decrease in the phasic pupil response to stimulation is observed during episodes of mind wandering [4]. These findings have been taken as evidence for a role of the LC-NE system in mind wandering.…”
Section: Mind Wandering and The Brainmentioning
confidence: 99%
See 3 more Smart Citations